Sex Differences in Academic Rank, Scholarly Productivity, NIH Funding, and Industry Ties Among US Academic Cornea Specialists - Chiam, Mckenzee (Am J Ophthalmol, 2020)
PURPOSE: This study analyzed sex differences among cornea specialists with regards to academic rank, scholarly productivity, National Institute of Health (NIH) funding, and industry partnerships. DESIGN: Cross-sectional study. METHODS: This was a study of faculty at 113 US academic programs. Sex, residency graduation year, and academic rank were collected from institutional websites between January-March 2019. H-indices and m-quotients were collected from the Scopus database. The NIH Research Portfolio Online Reporting Tool and Centers for Medicare and Medicaid Services databases were queried for data on NIH funding and industry partnerships. RESULTS: Of the 440 cornea specialists identified, 131 (29.8%) were females. The proportions of females and males at each academic rank (assistant: 69.5% vs. 41.8%; associate: 17.6% vs 21.0%; full professor: 13.0% vs. 37.2%) were not significant after adjusting for career duration (p=0.083, 0.459, 0.113, respectively). Females had significantly lower median h-indices [4.0, (Interquartile range (IQR) 7.0) vs. 11.0, (IQR 17.0); p<0.001] and shorter median career duration [12.0 (IQR 11.0) vs. 25.0 (IQR 20.0) years; p <0.001] than males, but similar median m-quotients (0.5 (IQR 0.8) vs. 0.5 (IQR 0.8); p=1.00). Sex differences in h-indices were not seen at each academic rank or career duration interval. Among NIH-funded investigators, median grant funding of was $1.6M (IQR 2.2M) for females and $1.2M (IQR 4.6M)(p=0.853) for males. Overall, 25.5% of females and 58.6% of males (p=0.600) had industry partnerships. CONCLUSION: Sex differences within academic ranks and h-indices are likely due to a smaller proportion of females with advanced career duration.